Peningkatan Kemampuan Manajemen Usaha Mikro Kecil dan Menengah Desa Merangkai dalam Pengelolaan Usaha Ekonomi Berbasis Potensi Lokal - Lie Othman; Kasmiruddin Kasmiruddin; Meyzi Heriyanto; Mandataris Mandataris; Ruzikna Ruzikna; Mariaty Ibrahim; Endang Sutrisna; Suryalena Suryalena; Syofiatul Safitri (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
This community service program aims to provide knowledge to the people of Merangkai Village which describes how to improve community business management capabilities in terms of managing, developing and improving economic businesses based on local potential. This information transfer was carried out in several stages, including socialization of the material to discussion sessions containing questions and answers and conveying the obstacles experienced. The application method used in this service is through lecture and discussion methods. In the first session, several materials in the fields of marketing, finance and human resources will be presented which are related to increasing the business management capabilities of village communities in managing, developing and improving economic businesses based on local potential. The next session will be opened with a discussion session in the form of questions and answers and also presenting obstacles so that solutions can be found. Apart from that, active community participation in all stages of activities is also the main focus in assessing the success of service. The results of the service showed a significant increase because the community service activities which were carried out face to face and in direct practice ran smoothly.